LINGUISTICS ANALYSIS OF SPECIALIZED VARIETIES AND REGISTERS OF ENGLISH LANGUAGE - Rasulova Nadira Baxadirovna (Journals Park Publishing, 2022)
The current article discusses linguistic and functional analysis of registers and specialized varieties of English languages. Using the definition from this paper, we think about specialized varieties as any registers that use language to investigate examples and meaning. This article opens up a wealth of possible examples, most of which are informative and easily understood on the context or perhaps in our everyday lives.
Keywords: style, register, formality, spectrum, modification, reduction, linguistic formulas.